An interview with Steven Rogers: thoughts on diversity and inclusion. Issue 5 (7th November 2019) - Foster, Mary Kuchta
Abstract : Research methodology: Personal interview. Case overview/synopsis: In an interview with Dr Mary Foster, Mr Steven Rogers, Finance Instructor at the Harvard Business School (HBS), discussed his views on diversity, inclusion and the value of teaching cases which feature black protagonists. Mr Rogers estimates that fewer than 1 percent of HBS' 10, 000 or so teaching cases feature a black executive as protagonist, or central decision-making figure, despite US Census estimates that about 9 percent of US companies are now black-owned. Mr Rogers decided to address this imbalance; he has lead the development of 24 business cases featuring African-American business people over the last two years. Complexity academic level: This article can be used to any undergraduate or graduate course where you would like to discuss diversity and inclusion.